Search for physics beyond the standard model in high-mass diphoton events from proton-proton collisions at root s=13 TeV - (:unkn) unknown (AMER PHYSICAL SOC, 2018)
A search for physics beyond the standard model is performed using a sample of high-mass diphoton events produced in proton-proton collisions at root s = 13 TeV. The data sample was collected in 2016 with the CMS detector at the LHC and corresponds to an integrated luminosity of 35.9 fb(-1). The search is performed for both resonant and nonresonant new physics signatures. At 95% confidence level, lower limits on the mass of the first Kaluza-Klein excitation of the graviton in the Randall-Sundrum warped extradimensional model are determined to be in the range of 2.3 to 4.6 TeV, for values of the associated coupling parameter between 0.01 and 0.2. Lower limits on the production of scalar resonances and modelindependent cross section upper limits are also provided. For the large extra-dimensional model of Arkani-amed, Dimopoulos, and Dvali, lower limits are set on the string mass scale M-S ranging from 5.6 to 9.7 TeV, depending on the model parameters. The first exclusion limits are set in the two-dimensional parameter space of a continuum clockwork model.
Keywords: PARTON DISTRIBUTIONS; DIMENSIONS; HIERARCHY